Amarogentin promotes osteoblast differentiation in oestrogen-deficiency-induced osteoporosis rats by modulating the Nrf-2/MAPK/ERK signalling pathway - Sirui Li; Xianlong Li; Feng He; Rui Jiao; Song Zhang; Zhihua Li (Archives of Medical Science, 2019)
Introduction The beneficial effect of amarogentin in the management of osteoporosis was determined using in vivo and in vitro methods.